Recurrent pyogenic granuloma within a port wine stain - Haneefa, Muhammed; Alshahrani, Mohammed; Shah, Sayed Agha A.; Alshahrani, Abdulmajeed (International Journal of Research in Dermatology, 2021)
Pyogenic granuloma (PG) is a common vascular growth usually seen on the face and extremities following trauma, drugs like retinoids, antineoplastic agents or pregnancy. PG and port-wine stain (PWS) represent different types of vascular lesions that may rarely occur in association. PG arising in a PWS is usually reported following trauma, pregnancy or laser treatment of PWS. Any growth in a long-standing vascular lesion creates panic in the patient and a challenge to the physician, especially in the head and neck area. We report a case of recurrent PG emerging de novo in three different locations within the same PWS in a 24 year old male. A review of literature about the coexistence of both conditions is presented here, together with dermoscopic features.